Menumbuhkan Resiliensi dan Kesehatan Mental Mahasiswa melalui Peningkatan Kapasitas Dosen Penasehat Akademik - saifuddin saifuddin; Amirullah Amirullah; Muhammad Aksha Wahda; Nurhasni Muis; Mario Mario (Humanis, 2026)
Abstract. Student mental health and resilience are crucial factors in determining academic success and preparedness to face life's challenges. However, academic advisors (PAs) have traditionally focused on administrative aspects rather than providing psychosocial support. This paper aims to identify and evaluate the knowledge and skills of academic advisors in fostering student resilience and mental health. The methods used included workshops, empathetic communication skills training, focus group discussions (FGDs), and ongoing mentoring. The results of the community service activities indicate increased knowledge and skills of academic advisors, strengthened student resilience, and the creation of a healthy and supportive academic environment.Keyword: resilience, mental health, academic advisor, supportive